THE IMPLEMENTATION OF INCLUSIVE EDUCATIONAL POLICIES OF ELEMENTARY SCHOOL IN SURAKARTA - Zakiah, Winda Greatta; Karsidi, Ravik; Yusuf, Munawir (Jurnal Pendidikan dan Pengajaran, 2021)
The inclusive education policies were created for children with special needs based on the equality principle. The implementation of inclusive education policies in each region has a different level of success. This research aims to find out how the implementation of inclusive educational policies in elementary school of Surakarta reviewed from Grindle’s policy implementation theory. Method used in this research is a combination method, which is involving 102 respondents and 9 informants from 12 inclusive schools. Data analysis used in this research are descriptive statistic and interactive modeling analysis of Miles and Huberman.The results showed that the implementation of inclusive education policy had a positive impact on the students and their environment, with the level of implementation of inclusive education is 76.8%, therefore the efforts are needed to optimize the implementation of inclusive education policies in the form of training for teachers and providing of supporting infrastructures. Keywords: Policy Implementation; Inclusive Education; Elementary School